Optical nonlinear refractive index of laser-ablated gold nanoparticles graphene oxide composite - Sadrolhosseini, Amir Reza; Muhammad Noor, Ahmad Shukri; Faraji, Nastaran; Kharazmi, Alireza; Mahdi, Mohd. Adzir (Hindawi Publishing Corporation, 2014)
Gold nanoparticles were prepared in graphene oxide using laser ablation technique. The ablation times were varied from 10 to 40 minutes, and the particle size was decreased from 16.55 nm to 5.18 nm in spherical shape. The nanoparticles were capped with carboxyl and the hydroxyl groups were obtained from Fourier transform infrared spectroscopy. Furthermore, the UV-visible peak shifted with decreasing of nanoparticles size, appearing from 528 nm to 510 nm. The Z-scan technique was used to measure the nonlinear refractive indices of graphene oxide with different concentrations and a gold nanoparticle graphene oxide nanocomposite. Consequently, the optical nonlinear refractive indices of graphene oxide and gold nanoparticle graphene oxide nanocomposite were shifted from  cm2/W to  cm2/W and from  cm2/W to  cm2/W, respectively.